2017
DOI: 10.1038/s41598-017-13928-6
|View full text |Cite
|
Sign up to set email alerts
|

Binding patterns of homo-peptides on bare magnetic nanoparticles: insights into environmental dependence

Abstract: Magnetic nanoparticles (MNP) are intensively investigated for applications in nanomedicine, catalysis and biotechnology, where their interaction with peptides and proteins plays an important role. However, the characterisation of the interaction of individual amino acids with MNP remains challenging. Here, we classify the affinity of 20 amino acid homo-hexamers to unmodified iron oxide nanoparticles using peptide arrays in a variety of conditions as a basis to identify and rationally design selectively binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 66 publications
3
53
0
Order By: Relevance
“…That the impact of ionic strength on separation depends on the salt selected was demonstrated by Procházková, who showed that phosphates have a strong effect and lead to a decreasing separation efficiency, whereas other anions did not [ 40 ]. We have also illustrated the high affinity of phosphate or citrate ions for the BION surface in previous work on adsorption of peptides and proteins [ 57 ], which explains the lower adsorption of other substances to the surface. Further adhesion experiments should deepen these findings.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…That the impact of ionic strength on separation depends on the salt selected was demonstrated by Procházková, who showed that phosphates have a strong effect and lead to a decreasing separation efficiency, whereas other anions did not [ 40 ]. We have also illustrated the high affinity of phosphate or citrate ions for the BION surface in previous work on adsorption of peptides and proteins [ 57 ], which explains the lower adsorption of other substances to the surface. Further adhesion experiments should deepen these findings.…”
Section: Discussionmentioning
confidence: 61%
“…Then, positively charged groups may meet negatively charged groups across the whole pH range, due to the complexity of the components present and the various dissociation constants (the so-called Lewis acid-base properties). Therefore, even when repulsion is expected from the zeta potential values (netto charge) of nanoparticles and algae, the patchwork model for charge distribution on the surface makes interaction possible, as recently presented by us [ 57 ]. Furthermore, the zeta potential of the particles depends strongly on the environmental conditions [ 40 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies we were able to show, that a binding of amino acids to bare iron oxide nanoparticles (BIONs), at ambient conditions close to pH 7, is mainly through the carboxy group and that peptides based on glutamate residues demonstrate a high affinity to BIONs . Moreover, a transfer to larger, more complex structures where this sequence can be used as affinity tag is possible.…”
Section: Introductionmentioning
confidence: 99%
“…The differences of affinity and binding capacity can be explained by strong electrostatic interactions between lysine and negatively charged materials such as cCNTs compared to the interactions with amphiphilic iron oxides [ 62 ]. However, iron oxide nanoparticles are also usually negatively charged as they get complexed by phosphate ions in PBS buffer [ 63 ]. l -lysine was chosen since this amino acid is much easier to detect with the TNBSA method compared to other amino acids [ 49 ].…”
Section: Resultsmentioning
confidence: 99%